Challenges and Cultural Resistance in Parikesit’s AI-Generated Music Content - Eka Dian Savitri (Jurnal Sosial Humaniora, 2026)
This article examines the entanglement of artificial intelligence (AI) and popular digital culture through a case study of the music video “Preman Anggaran” by the band Parikesit. The video features an AI generated female figure, modestly veiled yet styled in casual, tomboyish attire, performing socially charged rap-punk lyrics that critique political corruption and class inequality. Employing Norman Fairclough’s model of Critical Discourse Analysis (CDA) in conjunction with theoretical insights from Cultural Studies, this study interrogates the ideological, representational, and resistant dimensions embedded in both the textual and visual content. The analysis reveals how confrontational lexical choices, oppositional semantics, and direct narrative structures function as linguistic strategies of symbolic resistance. The production process, which relies on AI generated aesthetics, subverts conventional norms of visual representation and enables alternative forms of cultural expression. The video’s dissemination via digital platforms such as YouTube and TikTok exemplifies a non-institutional mode of circulation, while its reception demonstrates participatory engagement and affective resonance among politically conscious audiences. Ultimately, this study foregrounds the methodological relevance of CDA and cultural studies in navigating the cultural politics of algorithmically mediated expression, highlighting how AI can be mobilized as a vehicle for symbolic intervention and alternative articulation in contemporary popular culture.